Clinical, laboratory, and orbital imaging features of giant cell arteritis in comparison to non-arteritic anterior ischemic optic neuropath: a single center case series - Eldaya, Rami W.; Yeh, Yi-Hsien; Stunkel, Leanne; Parsons, Matthew S.; Van Stavern, Gregory P. (Frontiers in Ophthalmology, 2024)
BackgroundGiant cell arteritis (GCA) is the most common vasculitis in patients older than 50 years and is considered a “do not miss” diagnosis. However, it remains a diagnostic challenge given overlapping clinical syndromes such as non-arteritic anterior ischemic optic neuropathy (NAION) and poorly explored imaging findings.Materials and methodsIn this retrospective study between the time period of January 2013 and December 2021, a total of 13 consecutive patients with a pathological diagnosis of GCA and 8 patients with clinical diagnosis of NAION were isolated. Demographic and clinical data for each patient were collected, including pertinent laboratory data. Pertinent physical exam data was also collected, including fundoscopic exam and visual acuity. Two neuroradiologist assessed the orbital MRI imaging findings of GCA and NAION for the presence and characterization of imaging abnormalities. Assessment for potential relationship between GCA orbital findings, laboratory and visual outcomes was performed. Finally, comparison between GCA and NAION imaging findings was performed.Results13 GCA patients were assessed. 9 patients had abnormal orbital findings. Of these 8 patients had bilateral orbital involvement The most common imaging findings was perineuritis of the optic nerve sheath, present in 7 patients. In total, 8 NAION patients were assessed. All patients demonstrate optic nerve involvement. The Snellen test was converted to logmar, and visual acuity was assessed for both NAION and GCA for each eye at diagnosis and at the last follow-up. There was no statistical significance for either eye for both GCA and NAION at initial diagnosis and final follow-up. In the 4 GCA patients with normal MRI findings and 9 GCA patients with abnormal MRI findings, there was no statistical significance between initial presentation and final follow-up visual acuity.ConclusionGCA and NAION are potentially overlapping clinical syndromes with different treatment approach and poorly explored imaging findings. Our case series assesses the orbital imaging findings of both syndromes while noting different imaging pattern of both on MRI, which can serve as a potential tool to aid in diagnosis of both.